Penguatan Brand Awareness Melalui Good Visual E-Katalog Marketplace Pada Pelaku Umkm di Desa Tamansari Bogor - Dian Nurdiansyah; Sheilla Maharani; RR Lolita (Jurnal Informasi Pengabdian Masyarakat, 2024)
UMKM (Usaha Mikro, Kecil dan Menengah) are a category of businesses that operate on a smaller scale compared to large enterprises. Tamansari Village, located in Bogor Regency, is known as an area with a good level of MSME development and is able to compete through the products produced. However, from its development, there are still shortcomings that must be continuously improved and strengthened, especially in the visual of its products. The presence of digital transformation has become an actor of change and has a significant impact on MSME players, one of which encourages them to continue to be creative, especially from the visual aspects of the products produced and used in e-catalogs. The use of e-catalogs has become an important tool for MSMEs to adapt to the digital economy, giving them the tools to compete more effectively and maximize their growth potential. The method used in the research uses a mixed method with socialization and training methods, so that it is expected to be a key role in increasing the level of trust (Brand Awareness), especially in terms of the use of e-catalogs in the marketplace.